1. Doprowadż do najprostszej postaci
a)7ab *6a²b=
b)-4x² - 3 = 2x - x² - 4x = 5 =
c)(a - 3b - 4) +(11 a - 5b + 4 )=
d)(2a -3b - 2) - (-3a - b = 3)=
e) (5a-4b + 4c) - (3a - 2b - 3c) +(a-5b - c)=
f)5(2x² - 3x -5)=
g) -3x(-2x² - 4x = 1) + 5(x³-3x+2)=

1

Odpowiedzi

2010-02-28T19:11:31+01:00
A)7ab *6a²b= to jest najprostsza postać
b)-4x² - 3 = 2x - x² - 4x = 5 =-2x - x²
c)(a - 3b - 4) +(11 a - 5b + 4 )=a - 3b - 4 + 11a - 5b + 4 = 12a - 8b
d)(2a -3b - 2) - (-3a - b = 3)=2a - 3b - 2 + 3a + b + 3 = 5a - 2b + 1
e) (5a-4b + 4c) - (3a - 2b - 3c) +(a-5b - c)=5a - 4b + 4c - 3a +2b +3c + a - 5b - c = 3a - 7b + 6c
f)5(2x² - 3x -5)= 10x² - 15x - 25
g) -3x(-2x² - 4x = 1) + 5(x³-3x+2)=6x³ + 12x² + 3x + 5x³ - 15x + 10 = 11x³ + 12x² - 12x + 10
Mam nadzieję, że dobrze rozwiązałam te przykłady ;-]